The Product Space and the Middle-Income Trap Comparing Asian and Latin American Experiences - Jankowska, Anna (OECD Development Centre Working Papers, 2012)
Rapid and sustained economic growth in the emerging world has brought new members, notably China, into the group of middle-income countries. Reaching this level of income, however, has historically presented countries with a new set of challenges to development, resulting in slowing growth and an entrapment in what is known as the middle-income trap. Limited income convergence in Latin America has at least partly been due to its reduced capacity to engage in a structural transformation conducive to higher productivity. In contrast, emerging Asia offers a few examples of these ,virtuous. productive transformations. With these two references in mind, we build a comparative analysis based on the following points: First, we illustrate differences in the process of structural transformation, both with regard to sector productivity and employment absorption. Second, we adopt the Product Space methodology to compare the structural transformation that took place in both regions. Finally, we consider the role played by Productive Development Policies (PDP) in shaping the process of structural transformation, through a comparative review of these policies in Korea, Brazil and Mexico. In short, the analysis allows us to gauge the role that the economic specialisation of a country plays in facilitating transitions to more advanced stages of economic development